Pengaruh Budaya Kerja Etnik Terhadap Budaya Kerja Keadilan dan Keterbukaan Pns dalam Membangun Masyarakat Madani dan Demokrasi (Studi pada Pemerintah Kabupaten Pasaman Barat) - Frinaldi, Aldri; Ali Embi, Muhamad (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2011)
Justice and openness are among the values of working culture needed to support the development of civil society and democracy. Justice means that the works done by civil servants should be free from discrimination in any aspects, while openness means everyone who deals with the government offices should get transparent informations about things they deal with. This research aims to analyse the effects of the ethnical working culture to justice and openness in working culture of the civil servants in the Pasaman Barat Administrations. The research finds that ethnical culture tend to influence the civil servants in working justly and openly. To solve the problem, civil servants’ working culture in the government offices needs to change, which can be done by integrating the working culture set by the government with the positive ethnical culture and religious teachings in order to build democratic civil society. Kata kunci : budaya kerja etnik, Pegawai Negeri Sipil, masyarakat madani, demokrasi